2020
DOI: 10.1002/aoc.5401
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis method‐dependent photothermal effects of colloidal solutions of platinum nanoparticles used in photothermal anticancer therapy

Abstract: One of the most common anticancer therapies is photothermal therapy (PTT). The effectiveness of PTT depends on the photosensitizer being a molecule which is toxic for the cancer cells after electromagnetic wave irradiation. Therefore, a simulation of PTT was performed in this work on two colon cancer cells (SW480 and SW620) using platinum nanoparticles (Pt NPs). Interestingly, in the literature the dependence between the synthesis method and the photothermal properties of Pt NPs was not discussed. Consequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…While the % viability for cancer cells cultured with PtNPs and irradiated with 808 nm laser was 25% and 22% for SW480 and SW620, respectively. These findings may support future applications of biosynthesized PtNPs in photothermal cancer therapy [73]. Dobrucka et al reported the green synthesis of spherical and hexagonal PtNPs (4 nm) employing Ononis spinosa radix extract.…”
Section: Characterization and Biological Activities Of Ptnps Prepared Using Plant Extractsmentioning
confidence: 54%
“…While the % viability for cancer cells cultured with PtNPs and irradiated with 808 nm laser was 25% and 22% for SW480 and SW620, respectively. These findings may support future applications of biosynthesized PtNPs in photothermal cancer therapy [73]. Dobrucka et al reported the green synthesis of spherical and hexagonal PtNPs (4 nm) employing Ononis spinosa radix extract.…”
Section: Characterization and Biological Activities Of Ptnps Prepared Using Plant Extractsmentioning
confidence: 54%
“…In addition to being crucial for the production and application of PtNPs, the development of simple and environmentally friendly synthesis techniques also support the growing eld of green chemistry [21]. According to previous literature platinum nanoparticles were synthesized by using plant extracts Atriplex halimus [12], green tea powder [22], Saudi dates extract [23], Xanthium strumarium [24] Punica granatum [25], Nigella sativa L.[26], Antigonon leptopus [27], Garcinia mangostana L. [28], orange peel [29] etc. These plant extracts are made up of several distinct ingredients.…”
Section: Green Nanotechnologymentioning
confidence: 99%
“…Various mechanisms (physical, chemical-biological, or biological) are involved in radiosensitization; these mechanisms can overlap or act individually, depending, for example, on the type or energy of radiation [ 13 , 14 ]. The final effect of radiosensitization by NPs depends on the type of metal used, its size, shape, and the method of synthesis [ 15 , 16 , 17 , 18 ]. Exemplary, the generation of ROS by cells under the influence of NPs has already been known in the literature, e.g., for the widely used gold nanoparticles [ 19 ].…”
Section: Introductionmentioning
confidence: 99%